A STRUKTUR KOMUNITAS MAKROALGA DI PERAIRAN PANTAI NUNHILA DAN NUNBAUN DELHA, KOTA KUPANG - Rehatta, Beatrix Maureen (Indigenous Biologi : Jurnal Pendidikan dan Sains Biologi, 2023)
ABSTRACT The coastal waters of Nunhila and Nunbaun Delha, Kupang City, are one of the coastal areas that have high potential for macroalgae resources. However, this organism is very susceptible to changes in environmental conditions or ecological pressures both naturally, such as currents and seasons, which are triggering factors for changes in macroalgae habitat. This study aims to analyze the community structure of macroalgae in the coastal waters of Nunhila and Nunbaun Delha. This study uses the method of observation or direct observation in the field. The results showed that the composition of macroalgae found in the coastal waters of Nunhila and Nunbaun Delha from 3 divisions, Chlorophyta consisted of 4 species namely Chaetomorpha intestinali, Ulva reticulata, Enteromorpha intestinalis and Ulva lactuca. The Phaeophyta division consists of 2 species, namely Sargassum sp. and Padina australis. The Rhodophyta division consists of 3 types namely Gracilaria salicornia, Acanthophora specifera and Gigartina sp. The macroalgae diversity index value at Nunhila Beach was 0.89 and Nunbaun Delha was 0.89 (H') which was relatively low, the uniformity index at Nunhila Beach was 0.93 and Nunbaun Delha was 0.93 (E) which was evenly distributed and the dominance index (D) at Nunhila Beach 0.13 and Nunbaun Delha 0.14, neither species dominates. Keywords: Resources, macroalgae, Nunhila, Nunbaun Delha